The Use of Identity Card to Improve Students’ Speaking Skill - Indah Werdiningsih (Universitas Muhammadiyah Jember, 2017)
The study aimes to describe how a communicative activity through the useof identity card influences speaking skills of junior high schools students inBondowoso. Classroom Action Research (CAR) was implemented using a modelby Elliot to the first graders; 10 males and 15 females. It was done in two cycles;each of which consisted of two meetings. The researcher used collaborativeaction research with some of the English teachers. The data collection involvedTest of Speaking English and Speaking Rubric which evaluated fluency,pronunciation, vocabulary, and grammar. The finding showed the mean scoreof pretest reached 67.8 and that of posttest reached up to 70.2, resulting in asignificant improvement of 42 % in posttest 1 and 64% in posttest 2. Therefore,the criteria of success was achieved, indicated by the improvement of students’active participation, confidence and their fluency positively in speaking inpeer-interaction and discussion through the contents of Identity Card beforepracticing in front of the class. Hereby proposed some suggestions addressedto teachers and other researchers who wish to pursue related topics in futureresearch, concerning the importance of communicative activities using IdentityCard that can improve students’ enthusiasm and motivation.